Height, age at menarche and risk of hormone receptor‐positive and ‐negative breast cancer: A cohort study. Issue 11 (14th November 2012) - Ritte, Rebecca; Lukanova, Annekatrin; Tjønneland, Anne; Olsen, Anja; Overvad, Kim; Mesrine, Sylvie; Fagherazzi, Guy; Dossus, Laure; Teucher, Birgit; Steindorf, Karen; Boeing, Heiner; Aleksandrova, Krasimira; et al.
Abstract: Associations of breast cancer overall with indicators of exposures during puberty are reasonably well characterized; however, uncertainty remains regarding the associations of height, leg length, sitting height and menarcheal age with hormone receptor‐defined malignancies. Within the European Prospective Investigation into Cancer and Nutrition cohort, Cox proportional hazards models were used to describe the relationships of adult height, leg length and sitting height and age at menarche with risk of estrogen and progesterone receptor negative (ER‐PR‐) ( n = 990) and ER+PR+ ( n = 3, 524) breast tumors. Height as a single risk factor was compared to a model combining leg length and sitting height. The possible interactions of height, leg length and sitting height with menarche were also analyzed. Risk of both ER‐PR‐ and ER+PR+ malignancies was positively associated with standing height, leg length and sitting height and inversely associated with increasing age at menarche. For ER+PR+ disease, sitting height (hazard ratios: 1.14[95% confidence interval: 1.08–1.20]) had a stronger risk association than leg length (1.05[1.00–1.11]). In comparison, for ER‐PR‐ disease, no distinct differences were observed between leg length and sitting height. Women who were tall and had an early menarche (≤13 years) showed an almost twofold increase in risk of ER+PR+ tumors but no such increase in risk was observed for ER‐PR‐ disease. Indicators of exposures during rapid growth periods were associated with risks of both HR‐defined breast cancers. Exposures during childhood promoting faster development may establish risk associations for both HR‐positive and −negative malignancies. The stronger associations of the components of height with ER+PR+ tumors among older women suggest possible hormonal links that could be specific for postmenopausal women. Abstract : What's new? Adult height and early age at menarche are established risk factors for breast cancer. In this study, the authors examined these factors in relation to the hormone‐receptor status of breast tumors, with height divided into leg length vs. sitting height. They found that women who were tall and had an early menarche (≤13 years) had almost double the risk of developing estrogen/progesterone‐positive (ER+PR+) tumors. Leg length and early menarche were also associated with increased risk for receptor‐negative (ER‐PR‐) tumors. In addition, the data suggest possible hormonal links that could be specific for postmenopausal women.